2017
DOI: 10.1080/10810730.2017.1338802
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Literature on Effectiveness of Training in Emergency Risk Communication

Abstract: Although disaster preparedness training is regularly conducted for a range of health-related professions, little evidence-based guidance is available about how best to actually develop capacity in staff for conducting emergency risk communication. This article presents results of a systematic review undertaken to inform the development of World Health Organization guidelines for risk communication during public health and humanitarian emergencies. A total of 6,720 articles were screened, with 24 articles ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Evidence also shows that providing CERC training workshops, tabletop exercises, simulations, and ensuring capacity building in this regard to enhance emergency communication response may help strengthen local leaders in their communication during public health crises (12,26,27). Additionally, communicating plans from scenario modelling, which provide options for action (15) may clarify for its staff the hospital's rationale for resource reallocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also shows that providing CERC training workshops, tabletop exercises, simulations, and ensuring capacity building in this regard to enhance emergency communication response may help strengthen local leaders in their communication during public health crises (12,26,27). Additionally, communicating plans from scenario modelling, which provide options for action (15) may clarify for its staff the hospital's rationale for resource reallocation.…”
Section: Discussionmentioning
confidence: 99%
“…This study has demonstrated how CERC cuts across domains of hospital emergency response, such as command and control, communication, safety and security, triage, human resources, and logistics (21,32,33). CERC transcends all these domains at various scales, which suggests the need for coordination and collaboration in CERC (27). The interrelatedness of CERC and the domains of hospital emergency response highlight the need to consider communication at every domain of the hospital emergency response.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, operation-based exercises (such as drills, functional exercises, and field exercises) attempt to incorporate, to a lesser or greater degree, the front-line personnel, equipment, and physical spaces expected to be in play during an actual emergency (FEMA, 2019;Skryabina et al, 2017). A majority of studies on the effectiveness of training in emergency risk communication, in particular, conclude that the impacts of tabletop exercises and simulation for training include enhanced awareness, readiness, and knowledge (Miller et al, 2017).…”
Section: Benefits Of Scenarios and Simulations In Preparing For Disasmentioning
confidence: 99%
“…To increase the usefulness of the scenario, each response-and recovery-phase dilemma is followed by food for thought questions that are meant to prompt readers, reading as individuals or in training groups, to consider how they might respond to similar situations or how they might prevent similar problems or classes of problems from occurring in the first place. Like the studies of scenario-driven exercises (Skryabina et al, 2017) show, including those featuring emergency risk communication (Miller et al, 2017), the SPARS scenario is intended to prepare users for mitigating public health emergencies and managing MCM communication dilemmas more effectively. In the following sections, we outline the scenario environment and how the fictional outbreak begins.…”
Section: Create Charactersmentioning
confidence: 99%
“…Dalam kasus lain, studi literature review dalam bidang komunikasi juga digunakan untuk memetakan komunikasi yang berhubungan dengan topik tertentu atau bahkan studi interdisiplin. Hal itu sebagaimana Ann Neville Miller yang menggunakan pendekatan systematic review terhadap berbagai literatur tentang resiko komunikasi selama masa-masa krisis pelayanan kesehatan (Miller, 2017). Di bidang bisnis, Mabel Zvobgo dan T.C.…”
Section: Pendahuluanunclassified